THE EFFECT OF PRODUCT QUALITY, ENDORSEMENT INFLUENCER, AND PROMOTION OF THE PURCHASE DECISION OF VAVL BEAUTE SKINCARE IN KENDAL DISTRICT - Sukmawati Setyo Putri; Euis Soliha (Universitas Putera Batam, 2022)
This research measures the effect of product quality, influencer endorsement and promotion on purchasing decisions. This research was conducted on vavl beaute skincare consumers in Kendal Regency. The sampling technique for respondents is by applying a purposive sampling technique, using the following criteria: buyers or users who are at least 17 years old, buyers or users who have purchased or used vavl beaute skincare products. The data pooling method used a questionnaire that had been tested for validity and reliability. Data analysis in this research uses multiple linear regression analysis which intends to measure product quality, influencer endorsement and promotion variables on purchasing decisions. The research results show that influencer endorsements have no effect on purchasing decisions, while the results of research on product quality and promotion had a positive and significant effect on purchasing decisions.